Pengaruh Pola Pembiasaan Makanan Sehat Dan Bergizi Terhadap Konsentrasi Belajar Anak Usia Dini - Elin Parida; Husni; Desi Suryani (Bildung: Jurnal Ilmu Pendidikan, 2025)
Habituating healthy and nutritious eating patterns from an early age plays a strategic role in shaping cognitive development, particularly children's learning concentration. This study aims to analyze the effect of healthy eating habits on the learning concentration of early childhood at SPS TAAM Al Jamal, Bungursari, Kota Tasikmalaya. The approach used is descriptive quantitative with a correlational design, involving 40 children aged 4–6 years from groups A and B, as well as 6 accompanying teachers. Data were obtained through two main instruments, namely a healthy and nutritious eating habits questionnaire filled out by teachers and parents, and an observation rubric of children's learning concentration during learning activities. The results showed an average healthy eating habits score of 3.13 on a scale of 1–4 with a predominantly high category (69%), indicating that most children already have good and regular eating habits. Correlation analysis using the Pearson Product Moment test yielded an r value of 0.68 (p < 0.01), indicating a positive and significant relationship between healthy eating patterns and children's learning concentration levels. Children who maintain regular eating habits demonstrate longer attention spans, perseverance in tasks, and positive responses to teacher instructions. These results affirm that nutrition education programs based on healthy eating habits in early childhood education settings should be systematically integrated into learning activities, with active collaboration between teachers, parents, and educational institutions to enhance learning readiness and human resource quality from an early age.